Plant diversity under traditional agroforestry system of repong damar in Pesisir Barat District, Lampung Province, Indonesia - TRIO SANTOSO; RENDI PARIDDUAR; AFIF BINTORO (Society for Indonesian Biodiversity, 2023)
Abstract. Santoso T, Paridduar R, Bintoro A. 2023. Plant diversity under traditional agroforestry system of repong damar in Pesisir Barat District, Lampung Province, Indonesia. Biodiversitas 24: 4675-4683. repong damar, a traditional agroforestry system, benefits farmers and the environment; hence, it must be maintained. As a conservation endeavor and for long-term ecosystem management, repong damar's plant must be researched further. The study evaluated plant variety and composition in Pekon (Village) Pahmungan (PHG) and Pekon Negara Ratu Tenumbang (NRT) areas of Pesisir Barat Districts, Lampung Province, Indonesia, where both communities utilized repong damar for decades. The data was obtained systematically by marking 69 sample plots with sub-plots for different growth stages of 20 × 20 m for trees (S1), 10 x 10 m for poles (S2), 5 x 5 m for saplings (S3), and 2 x 2 m for seedlings (S4). A total of 56 species from 30 families were recorded in this study, which consisted of different life forms of trees (69.64%), shrubs (26.78%), and herbs (3.57%). Shorea javanica Koord. & Valet had the maximum IVI value in both study areas except for the S4 growth level. IVI values in PHM for S1, S2, and S3 were 136.41, 113.93 and 20.94, respectively. In NRT for S1, S2, and S3 were 89.25, 68.25 and 48.64, respectively. The farmers' preferences for Shorea javanica Koord and Valet are mainly caused by the fact that farmers have tapped its resin to provide their primary source of revenue, making them inherently dominant. Conversely, farmers neglecting Shorea javanica seedlings raises worries about its future viability, in addition to contemplating possible pests and diseases. Calculations of species diversity and evenness revealed moderate values and a generally even species distribution in both study areas. At the same time, Species richness calculation showed medium value and low in NRT. The three indices' values generate higher PMH ratings than NRT.